Novel TTC37 Mutations in a Patient with Immunodeficiency without Diarrhea: Extending the Phenotype of Trichohepatoenteric Syndrome - Rider, Nicholas L.; Boisson, Bertrand; Jyonouchi, Soma; Hanson, Eric P.; Rosenzweig, Sergio D.; Casanova, Jean-Laurent; Orange, Jordan S. (Frontiers in Pediatrics, 2015)
Unbiased genetic diagnosis has increasingly associated seemingly unrelated somatic and immunological phenotypes. We report a male infant who presented within the first year of life with physical growth impairment, feeding difficulties, hyperemesis without diarrhea, and abnormal hair findings suggestive of trichorrhexis nodosa. With advancing age, moderate global developmental delay, susceptibility to frequent viral illnesses, otitis media and purulent conjunctivitis were identified. Because of the repeated infections an immunological evaluation was pursued and identified impaired antibody memory responses following pneumococcal vaccine administration. Immunoglobulin replacement therapy and nutritional support were employed as mainstays of therapy. The child is now aged 12 years and still without diarrhea. Whole exome sequencing identified compound heterozygous mutations in the TTC37 gene, a known cause of the Trichohepatoenteric Syndrome (THES). This case extends the known phenotype of THES and defines a potential subset for inclusion as an immune overlap syndrome.